Determinants of Women's Employment Opportunities Entering the Demographic Bonus Era in South Sulawesi Province - Andriani, Shadry; Dwi Hastuti, Diah Retno; Praptani Adys, Himaya; Juardi (Jurnal Ilmu Ekonomi JIE, 2026)
This study aims to analyze the factors influencing women's employment opportunities in the context of the demographic bonus in South Sulawesi Province. The demographic bonus is characterized by an increasing proportion of the working-age population and is expected to strengthen economic development, particularly through women's active participation in the labor market. Multiple linear regression was used to test the influence of internet access (X1), minimum wages (X2), women's productive age (X3), average years of schooling (X4), access to workforce training (X5), and the gender development index (X6) on women's employment opportunities. The results indicate that internet access, women's productive age, and access to workforce training significantly affect women's employment opportunities in South Sulawesi, while minimum wages, average years of schooling, and the gender development index do not.